Analisis Ekonomi Dari Hukum Terhadap Undang-Undang Nomor 16 Tahun 2001 Tentang Yayasan - Pasaribu, Debora (Pelita Harapan University, 2006)
The growth of Yayasan (Foundation) in Indonesia has became wide in all public life major such as in social, religion, or humanity major. The existence of Yayasan is a need for the public who want an institution that has a social, religion or humanity character or aims. Yayasan is a tool that functionally can become a tool for the social, culture, and sains works. But lately, the facts show that public bulid a Yayasan not just for the social, religion or humanity matters but also to waive their obligation, such as waive pay the Â tax, to rich theirselves, and for the commercial interest that can make a damage to other interest. Beside this problems, there are other problems that occur such as, the activities that done by the Yayasan was not same as the Anggaran Dasar Yayasan and the disputes between the parties in the Yayasan. This problems can come about because there is no regulation that regulate this matters particularly, so with the birth of the UNDANG-UNDANG NOMOR 16 TAHUN 2001 TENTANG YAYASAN hope this problems can be solved.